Night-time light data based decoupling relationship analysis between economic growth and carbon emission in 289 Chinese cities. (October 2021) - Du, Xiaoyun; Shen, Liyin; Wong, Siu Wai; Meng, Conghui; Yang, Zhenchuan
Highlights: Light Time Light data is an effective source to assess decoupling performance. The decoupling performance in China has been improving for period of 1997 to 2018. Eastern cities of China have better decoupling performance than Western cities. Cities in each decoupling status need adopt tailor-made emission reduction policies. Abstract: Decoupling between urban economic growth (EG) and carbon emissions (CEs) has become a common goal globally for sustainable development. As the largest carbon emitter in the world, China has been attempting to reduce its carbon emissions in order to achieve the emission reduction goal promised to the world. This study examines the performance of decoupling between EG and CE in 289 Chinese cities by using the Tapio decoupling method. The Night Time Light (NTL) data are used for measuring the performance of EG. The NTL data are acquired from the data base Scientific Data. The carbon emission data are collected from the data sets released by CEADs. The main findings of this study are as follows. Firstly, Light Time Light data is an effective source to assess decoupling performance. Secondly, the decoupling performance in China has been improving during the study period. Thirdly, the cities in the Northeast and Eastern regions of China have better decoupling performance than those in Western and Central regions. This study shows a holistic picture of the decoupling status in China and provides supportive references for policy makers to make tailor-made measures for sustainable development in Chinese cities.